Retrospective cohort study of cancer incidence and mortality by HIV status in a Georgia, USA, prisoner cohort during the HAART era. Issue 4 (11th April 2016) - Zlotorzynska, Maria; Spaulding, Anne C; Messina, Lauren C; Coker, Daniella; Ward, Kevin; Easley, Kirk; Baillargeon, Jacques; Mink, Pamela J; Simard, Edgar P
Abstract : Objective: Non-AIDS-defining cancers (NADCs) have emerged as significant contributors to cancer mortality and morbidity among persons living with HIV (PLWH). Because NADCs are also associated with many social and behavioural risk factors that underlie HIV, determining the extent to which each of these factors contributes to NADC risk is difficult. We examined cancer incidence and mortality among persons with a history of incarceration, because distributions of other cancer risk factors are likely similar between prisoners living with HIV and non-infected prisoners. Design: Registry-based retrospective cohort study. Participants: Cohort of 22 422 persons incarcerated in Georgia, USA, prisons on 30 June 1991, and still alive in 1998. Outcome measures: Cancer incidence and mortality were assessed between 1998 and 2009, using cancer and death registry data matched to prison administrative records. Age, race and sex-adjusted standardised mortality and incidence ratios, relative to the general population, were calculated for AIDS-defining cancers, viral-associated NADCs and non-infection-associated NADCs, stratified by HIV status. Results: There were no significant differences in cancer mortality relative to the general population in the cohort, regardless of HIV status. In contrast, cancer incidence was elevated among the PLWH. Furthermore, incidence of viral-associated NADCs was significantly higher among PLWH versus those without HIV infection (standardised incidence ratio=6.1, 95% CI 3.0 to 11.7, p<0.001). Conclusions: Among PLWH with a history of incarceration, cancer incidence was elevated relative to the general population, likely related to increased prevalence of oncogenic viral co-infections. Cancer prevention and screening programmes within prisons may help to reduce the cancer burden in this high-risk population.